Writing Skills Development Through Think Pair Share in Elementary: Pengembangan Keterampilan Menulis melalui Think Pair Share di Sekolah Dasar - Asriyoni, Delliza; Aprizan; Andriani, Opi (Indonesian Journal of Innovation Studies, 2025)
Background (general): Writing is a fundamental literacy skill in elementary education, yet many students still face difficulties in expressing ideas coherently. Background (specific): At SDN 219/II BTN Lintas Asri, most sixth-grade students had not achieved the minimum mastery criteria in writing, with weaknesses in structuring sentences and paragraphs. Knowledge Gap: Prior studies have focused on specific text genres or lower grade levels, leaving limited exploration of collaborative learning approaches in higher elementary classes. Aim: This study aims to examine how the Think Pair Share (TPS) model supports the development of students’ writing abilities. Results: Using Classroom Action Research with two cycles, findings showed notable progress in both teacher and student activities. Teacher observation scores increased from 82.35% to 100%, while student observation scores improved from 56.9% to 94.54%. The proportion of students achieving the minimum writing score rose from 36.36% to 81.82%. Qualitative evidence demonstrated clearer sentence structures, more coherent ideas, and increased confidence in writing. Novelty: This study highlights the effectiveness of TPS not only in enhancing student performance but also in fostering collaboration, critical thinking, and learner engagement in writing tasks. Implications: TPS can be adapted in elementary classrooms as a practical strategy to strengthen literacy skills and encourage active participation in language learning. Highlight Improved students’ writing performance and classroom participation. TPS fostered collaborative learning and critical thinking. Writing outcomes showed higher mastery and confidence. Keyword Writing Skills, Think Pair Share, Elementary School, Classroom Action Research, Student Participation